Comparison of sport massage and combination of cold water immersion with sport massage on decrease of blood lactic acid level - N.F. Romadhona (IOP Publishing Ltd., 2019)
Recovery is an attempt to reduce blood lactic acid levels and make the body recover after physical exercise. The effect of cold water immersion (15°C) and sport massage combined with decreasing blood lactic acid level is still unknown. The subjects assigned to 3 groups, K1 group for recovery sport massage, K2 recovery group for combination of cold water immersion (15°C) with sport massage and K3 control group. Both groups performed sub-maximal physical exercise by doing a fast walk on the treadmill to reach (80% HRM) and then maintained for 5 minutes, followed by recovery process. ANOVA test of lactic acid level post treatment which shows there was a significant difference in the decrease of lactic acid level. The paired t-test of each group showed significant results in sports massage group (p = 0,001), combination cold water immersion (15°C) with sport massage group (p = 0,000) and a control group (p = 0,002). Recovery by soaking in contrasting waters, which result in alternating vasoconstriction and vasodilation, is considered to act in a manner similar to muscle pumping (vaso-pumping). Recovery by means of sport massage and combination of cold water immersion (15°C) with sport massage can decrease blood lactic acid levels.